2020
DOI: 10.26656/fr.2017.4(5).172
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial activities in the fruit peel, flesh and seed of Ceri Terengganu (Lepisanthes alata Leenh.)

Abstract: Malay cherry fruit or locally known as Ceri Terengganu (Lepisanthes alata Leenh.) is a local tropical exotic fruit and it is native to Malaysia. The Ceri Terengganu tree is widely distributed in the east coast of Peninsular Malaysia particularly in Terengganu, Pahang and Johor and commonly cultivated as an ornamental plant in the villages and gardens. A limited number of studies had been done on the proximate analysis and postharvest quality of Ceri Terengganu fruit, but the studies on the antioxidant and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Total phenolic contents were determined using the Folin Ciocalteau reagent by Looi et al (2020) with some modifications. Briefly, the sample, distilled water, sodium carbonate, and Folin-Ciocalteau reagent mixture were held for 2 h before the absorption was measured at 765 nm.…”
Section: Total Phenolic Contentsmentioning
confidence: 99%
“…Total phenolic contents were determined using the Folin Ciocalteau reagent by Looi et al (2020) with some modifications. Briefly, the sample, distilled water, sodium carbonate, and Folin-Ciocalteau reagent mixture were held for 2 h before the absorption was measured at 765 nm.…”
Section: Total Phenolic Contentsmentioning
confidence: 99%
“…The geographical distribution of Lepisanthes is broad, extending from India and Sri Lanka in the west to Malaysia, the Philippines, Vietnam, and Papua New Guinea in the east. In Southeast Asia, six of these species are native to Malaysia and can be found flourishing in the wild as well as in orchards (i.e., L. alata , L. amoena, L. fruticosa, L. senegalensis, L. rubiginosa, and L. tetraphylla ) [ 5 , 6 ]. The tropical rainforest is the natural habitat of Lepisanthes species, which grows from lowland to lower montane forest at 1800 m above sea level.…”
Section: The Botany Of Genus Lepisanthesmentioning
confidence: 99%
“…Looi et al [ 5 ] compared the in vitro antioxidant activity of 60% ethanolic extract of L. alata ’s peel, flesh, and seed using both DPPH and ABTS assays. Butylated hydroxytoluene (BHT), vitamin E, and vitamin C were selected as the positive controls for DPPH methods, while Trolox was the positive control for the ABTS method.…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The caffeates substituent are attached to C-3 of hopane while coumarates are connected to lupane skeletons. On the other hand, triterpenoid saponins were isolated to give eight known compounds (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These compounds usually form a glycosidic bond to its glycine namely glucose, arabinose, rhamnose and xylose.…”
Section: Terpenesmentioning
confidence: 99%
“…The phytochemical screening of this genus has shown the presence of alkaloids, flavonoids, tannins, saponin triterpenoids, phenolics and glycosides. 6,[12][13] Pharmacological studies of the extracts showed the presence of anticancer, antimicrobial, antiacetylcholinesterase,…”
mentioning
confidence: 99%